Implementasi Nilai-nilai Pendidikan Pesantren dalam Meningkatkan Ketahanan Mental Santri - Muhammad Mushfi El Iq Bali; Mohammad Fajar Sodik Fadli (PALAPA, 2019)
Education is the main investment in shaping a person's character, personality and mentality. In this globalization era, character, personality and mental education are eroded by western education. Islamic boarding school education is a top priority in shaping a person's character, personality and mentality to be better. Islamic boarding school education provides optimal and effective time in implementing religious and moral values. The capacity of pesantren as a religious institution in its history has succeeded in realizing the order of life of religious communities, with a fundamental and complex understanding of Islam. The values of Islamic education that are so complex from values, aqeedah, monotheism, morality and science in this era of globalization have been fulfilled in Islamic boarding schools. Therefore Islamic boarding school education applies the values of quality Islamic education to establish the mentalty resilience of santri (islamic student), Islamic boarding school plays an important role in making a person become a human who is civilized (insanul kamil).